PENGARUH BRAND AMBASSADOR, HARGA DAN DESAIN PRODUK DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MEDIASI TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOP SHOPEE - Nurhaliza, Widi; Ampa, Andi Tenri; Mustari, Mustari; Subur, Hikmayani; Tadampali, Andi Caezar To (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to see and find out how the purchasing decisions of students of the Faculty of Economics and Business, Makassar State University with the factors of brand ambassadors, price and product design. The type of research used is quantitative research using a survey method with instruments in the form of questionnaires and methods. This study used the Structural Equation Model (SEM) with a sample of 133 respondents. The results of this study indicate that brand ambassadors have a positive and significant influence on purchasing decisions, prices have a positive and significant influence on purchasing decisions, product design has a positive and significant influence on purchasing decisions, product quality has a positive and significant influence on purchasing decisions, brand ambassadors have a positive and significant influence on product quality, prices have a positive and significant influence on product quality, product design has a positive and significant influence on product quality